PERFORMANCE COMPARISON OF CLUSTER-BASED PROTOCOLS IN WIRELESS SENSOR NETWORKS - Simimol Surendran; Ajitsinh Jadhav (International Journal of Innovations in Engineering Research and Technology, 2021)
To reduce the energy consumption is an important topic in the Wireless Sensor network(WSN).Many protocols have been designed for improving energy efficiency of the network. Clustering protocols have been proved to be one of the energy-efficient protocols in WSN. One of the basic and most popular protocols designed using the clustering approach is the LEACH (Low-Energy Adaptive Clustering Hierarchy).However, LEACH undergoes an issue of bad distribution of cluster heads, which is overcomeby implementing a technique of selecting smart cluster headin LEACH known as SCHS (Smart Cluster Head Selection)